PENGEMBANGAN VIDEO ANIMASI BERBANTUAN DORATOON PADA MATERI SUMBER ENERGI DI SEKITAR KITA - Marshella Addleia Supriyatna; Yuli Mulyawati; Lufty Hari Susanto (STKIP Subang, 2026)
This study aims to develop animated videos assisted by Doratoon on the material of energy sources around us in class III SDN Polisi 5 Bogor with a total of 29 students. The development of this product uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). In this study, validation tests were carried out by several experts, namely media experts, language experts and material experts. The final validation results by the media obtained a percentage of 100% with very feasible criteria. The final validation results by language experts obtained a percentage of 100% with very feasible criteria. The validation results of lecturer material experts obtained a percentage of 90% with very feasible criteria. The validation results by teacher material experts obtained a percentage of 100% with very feasible criteria. For the average value of N-Gain, learning outcomes obtained 0.78 with high criteria. The results show that animated videos assisted by Doratoon on the material of energy sources around us are very feasible to be developed and effective in the learning process.